Penerapan Penilaian Dampak Heritage Warisan Arsitektur Rumah Jawa di Desa Wisata Brayut dalam Pengelolaan Berkelanjutan - Maria Kinanthi (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
Heritage impact assessment is used to communicate negative impacts on important values of heritage attributes that need to be preserved. Therefore, should used integrated, and sustainable risk management strategies will be found. This study used qualitative methods with descriptive analysis techniques. Five stages were carried out, including observation, interviews, determining the main attributes of the property, analyzing the level of positive and negative impacts, and finally, providing recommendations for mitigation strategies. The results showed that implementated strategies as follow a). stipulating the principles and concepts of heritage preservation that involve protection, adaptive reuse and sustainable development; b). increase public awareness; c). long-term planning through tourism activities and traditional activities.